2021
DOI: 10.1038/s41598-021-99415-5
|View full text |Cite
|
Sign up to set email alerts
|

Apoplastic effector candidates of a foliar forest pathogen trigger cell death in host and non-host plants

Abstract: Forests are under threat from pests, pathogens, and changing climate. A major forest pathogen worldwide is the hemibiotroph Dothistroma septosporum, which causes dothistroma needle blight (DNB) of pines. While D. septosporum uses effector proteins to facilitate host infection, it is currently unclear whether any of these effectors are recognised by immune receptors to activate the host immune system. Such information is needed to identify and select disease resistance against D. septosporum in pines. We predic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…In our previous work, two small, secreted candidate effector proteins from D. septosporum NZE10, Ds70694 and Ds70057, triggered cell death in the non-host species N. tabacum and N. benthamiana (Hunziker et al, 2021). Both proteins are homologs of Ecps from F. fulva and are part of two different protein families, Ecp20 and Ecp32, respectively (Mesarich et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work, two small, secreted candidate effector proteins from D. septosporum NZE10, Ds70694 and Ds70057, triggered cell death in the non-host species N. tabacum and N. benthamiana (Hunziker et al, 2021). Both proteins are homologs of Ecps from F. fulva and are part of two different protein families, Ecp20 and Ecp32, respectively (Mesarich et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Following on from a previous study in which DsEcp20-3 and DsEcp32-3 were shown to elicit cell death in the non-host plants N. benthamiana and N. tabacum using ATTAs (Hunziker et al, 2021), we set out to determine whether other family members of both D. septosporum and F. fulva could elicit the same response. To achieve this, all Ecp20 and Ecp32 family members were transiently expressed in N. benthamiana and N. tabacum using ATTAs, and the percentages of plant responses in three different categories recorded: strong cell death, weak cell death and no cell death (Figure 5; Supplementary Figure S6).…”
Section: Other Members Of the Ecp20 And Ecp32 Families From D Septosp...mentioning
confidence: 99%
See 3 more Smart Citations